Chrzcielnica z Kościoła św. Krzyża i chrzty w Krakowie doby jagiellońskiej .......... 397 - Sowała, Wojciech (Plus ultra: Studia z historii sztuki ofiarowane Profesorowi Markowi Walczakowi w 60. rocznicę urodzin, 2025)
THE BAPTISMAL FONT IN THE CHURCH OF THE HOLY CROSS AND BAPTISMS IN CRACOW DURING THE JAGIELLONIAN ERAThe bronze baptismal font in the Church of the Holy Cross in Cracow is one of the best examples of Cracow’s 15th-century casting work. Richly decorated with saint’s figures, it was created in Jan Freudental’s workshop in 1423. Unfortunately, only the bowl of the original work, has survived to our times. The base and cover dates from the late 19th century. This article presents the object in the context of other bronze medieval baptismal fonts from the Lesser Poland region, ensuring its efficiency, functionality, ideology, and iconography.